EVALUATION OF ANTIBACTERIAL ACTIVITY OF CRUDE EXTRACTS OF GASTROPOD, Harpa davidis,RODING 1798 ,FROM KANYAKUMARI COAST AGAINST ISOLATED HUMAN AND FISH PATHOGENS. - Giftson, Hermina; Patterson, Jamila (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To screen the antibacterial drugs from different solvent extracts of tissue of marine gastropod Harpa davidis against clinically isolated human pathogenic bacteria and fish pathogens and to evaluate the biochemical composition and functional groups of the sample. Methods: Crude extract of gastropod was tested for inhibition of bacterial growth. Antibacterial assay was performed by disc diffusion method. Biochemical composition of the tissue extract was analyzed using standard procedures. Moreover, Fourier transform infrared spectroscopy (FTIR) spectrophotometry analysis was also studied. Results: The antimicrobial activity was measured based on the zone of inhibition around the disc impregnated with gastropod extract. The maximum zone of inhibition (10 mm) was observed against human pathogen Bacillus cereus in the crude methanol extract of H. davidis and the minimum zone of inhibition (2 mm) was noticed against Shigella dysentriae in the crude ethanol extract of H. davidis. In the case of fish pathogens, a maximum zone of (5 mm) was observed by methanol extract against Vibrio anguillarum and a minimum zone of 2 mm was observed by ethanol extract against V. alginolyticus. The proximate composition, such as protein, carbohydrate, and lipid contents of H. davidis tissue, was estimated. The results of this study revealed that the protein composition was high 38.42% followed by carbohydrate 9.61% and lipid 3.14%. FTIR spectrum of the sample H. davidis showed that 6 major peaks were shown at 3560.35, 2925.81, 2854.45, 1554.52, 1413.72, and 667.32/cm showing the presence of carboxyl, alkanes, aromatic, and alkyl functional groups. Conclusion: The present study indicated that the marine mollusc collected from the Kanyakumari coast possessed several bioactive compounds of therapeutic interest. Further studies are going onto isolate specific compounds and to study the biological activities present in them. Keywords: Harpa davidis, Human pathogens, Fish pathogens, Fourier transform infrared spectroscopy.